Focused Antenatal Care in urban Ghana: A qualitative study into physical accessibility of maternal health services in Kwabre East Municipality - Asafo, Akowuah Jones; Owusu, Kwarteng Bernard (Clinical Journal of Obstetrics and Gynecology, 2019)
Background: Accessibility to healthcare is a major component of primary health care campaign for maintaining population health. Owing to this, the government of Ghana has instituted the free maternal care and focused antenatal care policies into the maternal health care policies to woefully control maternal mortality, morbidity and to ensure improved access, quality and continuous ANC use among pregnant women. Despite these interventions, pregnant women in the Kwabre East Municipality do not fully use ANC services as recommended by the World Health Organization. Methods: Using an in-depth interview and two focus groups conducted with women of reproductive age (15-49) in the Kwabre East Municipality. The study investigated women’s opinions, perceptions and experiences on their ANC visits. Results: The study revealed that physical accessibility and the social context of pregnant women continue to influence their ANC use even after the introduction of the free maternal care and focused antenatal care policies. Conclusion: The study suggests that in order to fully utilize ANC visits as recommended by the WHO in the Kwabre East Municipality, the Municipal Health Directorate should liaise with collaborating stakeholders if not eliminating to limit the influence of restrictive factors to women’s quest of using ANC. It is further recommended that management do away with hindrances that delay women who seek for ANC services in health facilities and adopt strategies and procedures that aim at increasing ANC uptake.